2020
DOI: 10.2196/23184
|View full text |Cite
|
Sign up to set email alerts
|

Social Network Analysis of Intensive Care Unit Health Care Professionals Measured by Wearable Sociometric Badges: Longitudinal Observational Study

Abstract: Background Use of wearable sensor technology for studying human teamwork behavior is expected to generate a better understanding of the interprofessional interactions between health care professionals. Objective We used wearable sociometric sensor badges to study how intensive care unit (ICU) health care professionals interact and are socially connected. Methods We studied the face-to-face interaction data of 76 healthcare professionals in th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Since some health conditions require continuous monitoring, sensor output constancy should be considered, especially for ICU patients [ 92 , 93 , 94 ]. For instance, drift in calibration to prolonged use, such as the accumulation of individually minuscule errors in accelerometers, may lead to less reliable output data.…”
Section: Discussionmentioning
confidence: 99%
“…Since some health conditions require continuous monitoring, sensor output constancy should be considered, especially for ICU patients [ 92 , 93 , 94 ]. For instance, drift in calibration to prolonged use, such as the accumulation of individually minuscule errors in accelerometers, may lead to less reliable output data.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted with professionals working in the intensive care unit of a university hospital in Japan found that the interactions between nursing professionals were significantly more active than those of other professionals. Moreover, nurses were also the category that interacted the most with other categories [ 36 ]. A similar result was found in another investigation in Japan, where the structure of a community clinical service network indicated nurses as the central actor in the social network [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further network development may result in a transition into more integrated, co-ordinated networks. Several recent studies analysed hospital networks in health care as co-ordinated networks [ 12 , 43 , 44 ]. In our study, we classified networks H and J in this stage because horizontal and vertical links have been created between organisational units.…”
Section: Discussionmentioning
confidence: 99%